Identification techniques for highly boosted W bosons that decay into hadrons - (:unkn) unknown (SPRINGER, 2014)
In searches for new physics in the energy regime of the LHC, it is becoming increasingly important to distinguish single-jet objects that originate from the merging of the decay products of W bosons produced with high transverse momenta from jets initiated by single partons. Algorithms are defined to identify such W jets for different signals of interest, using techniques that are also applicable to other decays of bosons to hadrons that result in a single jet, such as those from highly boosted Z and Higgs bosons. The efficiency for tagging W jets is measured in data collected with the CMS detector at a center-of-mass energy of 8TeV, corresponding to an integrated luminosity of 19.7 fb(-1). The performance of W tagging in data is compared with predictions from several Monte Carlo simulators.
Keywords: Jets; Jet physics; Hadron-Hadron Scattering